Decomposing the Causes for Niche Differentiation Between Species Using Hypervolumes - Carvalho, José Carlos; Cardoso, Pedro (Frontiers in Ecology and Evolution, 2020)
Hutchinson’s n-dimensional hypervolume concept holds a central role across different fields of ecology and evolution. The question of the amount of hypervolume overlap and differentiation between species is of great interest to understand the processes that drive niche dynamics, competitive interactions and, ultimately, community assembly. A framework is proposed to decompose overall differentiation among hypervolumes into two distinct components: niche shifts and niche contraction / expansion processes. Niche shift corresponds to the replacement of space between the hypervolumes occupied by two species, whereas niche contraction / expansion processes correspond to net differences between the amount of space enclosed by each hypervolume. A procedure to implement non-continuous trait data in the estimation of n-dimensional hypervolumes is proposed. Hypervolumes were constructed for three Darwin' finches, Geospiza conirostris, Geospiza magnirostris and Geospiza difficilis using intraspecific trait data. Results showed that significant niche shifts, not niche contraction, occurred between G. conirostris and G. magnirostris in Genovesa island, where they live in sympatry. This means that G. conirostris occupied a different niche space and not a reduced space on Genovesa. G. difficilis was well differentiated from the other two species. The proposed framework allows disentangling different processes underlying niche partitioning between coexisting species. This framework offers novel insights to understand the drivers of niche partitioning strategies among coexisting species.